2007
DOI: 10.1021/ja073587r
|View full text |Cite
|
Sign up to set email alerts
|

Charge Transport Parameters of the Pentathienoacene Crystal

Abstract: Pentathienoacene, the thiophene equivalent of pentacene, is one of the latest additions to the family of organic crystal semiconductors with a great potential for use in thin film transistors. By using density functional theory and gas-phase ultraviolet photoelectron spectroscopy, we investigate the microscopic charge transport parameters of the pentathienoacene crystal. We find that the valence band exhibits a stronger dispersion than those in the pentacene and rubrene single crystals with marked uniaxial cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
114
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(124 citation statements)
references
References 67 publications
9
114
1
Order By: Relevance
“…(9) and (11). Previous research [65] suggested a method to evaluate the intermolecular geometric relaxation energy based on the electronic polarization P + that results from the interaction of the excess charge with both permanent and induced multipoles in surrounding molecules, and the P + can be obtained from the ultraviolet photoelectron spectroscopic (UPS) data of gas and solid phases [66,67]. Herein, we pay our attention to indicate which kind of organic semiconductor complex 1 and 2 could be function as, the n-type or p-type and which one has better functions.…”
Section: Theory and Computational Methodsmentioning
confidence: 99%
“…(9) and (11). Previous research [65] suggested a method to evaluate the intermolecular geometric relaxation energy based on the electronic polarization P + that results from the interaction of the excess charge with both permanent and induced multipoles in surrounding molecules, and the P + can be obtained from the ultraviolet photoelectron spectroscopic (UPS) data of gas and solid phases [66,67]. Herein, we pay our attention to indicate which kind of organic semiconductor complex 1 and 2 could be function as, the n-type or p-type and which one has better functions.…”
Section: Theory and Computational Methodsmentioning
confidence: 99%
“…The inclusion of an alkyl substitute, a weakly electron-donating group, at the b termini of thienoacenes had little influence on the EAs, but an obvious influence on the VIPs of tetrathienoacene (7) and pentathienoacene (13), as evidenced in the comparison of the EA and VIP values of alkyl-substituted oligothienoacenes with those of their unsubstituted analogues. As shown in Table 1, the deviations in the EAs between oligothienoacenes and their corresponding alkyl-substituted analogues were smaller than 0.1 eV, whereas the VIP values of compounds 11 and 17 were about 0.3 eV smaller than their counterparts that did not contain alkyl substituents (7 and 13, respectively).…”
Section: Vertical Electron Affinities Vertical Ionization Potentialsmentioning
confidence: 99%
“…For example, Bredas et al investigated the charge-transport parameters of the pentathienoacene (5TA) crystal and they calculated that the intrinsic hole-mobility might be larger in the 5TA crystal than that in high-mobility pentacene in band regime. [13] Moreover, Yamada et al showed that benzo-annulated 5TA, a 5TA derivative with a co-facial p-stacking structure, exhibited hole-mobilities as high as 0.5 cm 2 V À1 s À1 for single-crystal FETs. [8] Recently, many synthetic approaches to structural modification have led to the modulation of the electronic structures and modes of crystal packing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 in the supplemental material). 8,37,[39][40][41][42][43][44] It should be noted here that the reorganization energies of organic molecules calculated from potential energy surface are nearly the same as those from the normal mode expansion. 42 The HOMO/LUMO wave functions shown in Figs.…”
Section: Resultsmentioning
confidence: 99%